Co-Culture antara Sunda dan Batak dalam Film Ngeri Ngeri Sedap - Liza Erica Panjaitan (Laboratory of Anthropology Department of Cultural Science Faculty of Halu Oleo University, 2023)
The film Ngeri Ngeri Sedap highlights Batak culture with the conflict between Batak parents and their eldest son who wants to marry a woman from a Sundanese ethnic background. This research aims to look at the co-culture process that occurs between these cultures to analyze the phenomenon of marriage between dominant cultures in Indonesia, such as the Batak tribe. This research uses a content analysis method with a conventional content analysis approach by looking at the process of assimilation, accommodation, and separation between the Domu character and the Neni character. The findings of this research are that the character Neni carries out assertive assimilation to approach and adapt to Domu by manipulating stereotypes by carrying out a procession of giving the Batak surname before getting married using the Batak wedding process. Neni also accommodated her ability and communication skills with Pak Domu which was shown by using the nickname